The Relationship Between Transformational Leadership and Teacher Organizational Commitment in Secondary Schools in Padang City, West Sumatra - Ramadhini, Kurniati (International Journal Labs, 2024)
Education plays an important role in improving the quality of a country's human resources. In Indonesia, teacher quality is a major concern, as seen from the results of the Teacher Competency Test (UKG) in 2012 to 2015. Of the 1.6 million participants, 1.3 million teachers did not meet the minimum competency standards, which of course has an impact on the quality of education. To overcome this problem, attention must be focused on improving the quality of teachers, not just on changing the curriculum. Another challenge is the low level of active participation of teachers in school activities and technology adaptation during the COVID-19 pandemic. Many teachers lack enthusiasm and innovation in implementing online learning. In this context, organizational commitment becomes important which is influenced by factors such as leadership style. This study examines the relationship between transformational leadership and organizational commitment among junior high school teachers in Padang City, West Sumatra. Using a quantitative approach, data from 159 teachers in six schools were analyzed using SPSS version 26.0. The results showed that transformational leadership significantly influenced organizational commitment. This study emphasizes the importance of enhancing transformational leadership in strengthening teachers' organizational commitment. Educational organizations are expected to utilize these findings to improve teacher quality and support national education goals. This research also contributes knowledge to the world of education, especially for educational organizations in Indonesia.